The sequence stratigraphic evolution of the Sturgeon Lake bank, central Alberta, Canada and its regional implications. - Kahmann-Robinson, Julia A. (2006)
Sturgeon Lake South (SLS) is an isolated Devonian (Late Frasnian) platform located within the Western Canada Sedimentary Basin (WCSB). Stratigraphic correlation of the Leduc Formation across the WCSB reveals a dominantly backstepping stratal geometry. The Sturgeon Lake South bank complex is composed of 12 retrogradationally stacked depositional sequences. Sequences 1 and 2 prograde, and sequences 3-6 backstep. Bank formation and stratal geometries are controlled by eustatic sea level fluctuations in concert with: 1) a northeasterly paleowind direction that induced highly aggradational windward margins, 2) antecedent topographic highs (e.g., Peace River Arch) that induced progradational margins and, 3) sediments derived from the Antler Orogeny that increased marine turbidity and influenced the termination of platform growth. Within the Leduc Formation at SLS, dolomitization is pervasive and fabric destructive, enhances reservoir quality, and is not facies specific. Dolomitization most likely occurred within the burial environment.